The fashion forecasters : a hidden history of color and trend prediction - Blaszczyk, Regina Lee; Wubs, Ben (Bloomsbury Academic, 2018)
The fashion business has been collecting and analyzing information about colors, fabrics, silhouettes, and styles since the 18th century - activities that have long been shrouded in mystery. The Fashion Forecasters is the first book to reveal the hidden history of color and trend forecasting and to explore its relevance to the fashion business of the past two centuries. It sheds light on trend forecasting in the industrial era, the profession's maturation during the modernist moment of the 20th century, and its continued importance in today's digital fast-fashion culture. Based on in-depth archival research and oral history interviews, The Fashion Forecasters examines the entrepreneurs, service companies, and consultants that have worked behind the scenes to connect designers and retailers to emerging fashion trends in Europe, North America, and Asia. Here you will read about the trend studios, color experts, and international trade fairs that formalized the prediction process in the modern era, and hear the voices of leading contemporary practitioners at international forecasting companies such as the Doneger Group in New York and WGSN in London. Probing the inner workings of the global fashion system, The Fashion Forecasters blends history, biography, and ethnography into a highly readable cultural narrative.